Exploring the Prevalence of Cardiovascular Risk Factors Among Healthcare Workers - Benjamin Champ Thomas; Maryam Zainal; Mohd Jaamia Qaadir Mohd Badrin; Nurkhairul Bariyah Baharun (Asian Journal of Medicine & Health Sciences, 2024)
Cardiovascular disease stands as the foremost cause of mortality worldwide. Multiple physiologic factors such as obesity, hypertension, hyperlipidaemia, and hyperglycaemia are strongly associated with the increased risk of developing cardiovascular diseases. Healthcare professionals are susceptible to cardiovascular disease due to lifestyle and occupational factors. This study aims to determine the prevalence of cardiovascular disease risk factors among healthcare workers in Pejabat Kesihatan Daerah Segamat (PKD Segamat). A retrospective quantitative study was conducted by obtaining data measurements of height, weight, blood pressure, fasting blood glucose, cholesterol, and triglyceride levels of 378 healthcare workers. The workforce was categorized into management & professional, executor, and administrative & support groups. Only 11.9% of healthcare workers were considered healthy, whereas the majority (35.7%) had at least one cardiovascular disease risk factor. Obesity was prevalent at 33.3%, with systolic hypertension at 3.2% , diastolic hypertension at 2.9% , hyperglycaemia at 4.5%, hypercholesterolemia at 55% and hypertriglyceridemia at 14%. The prevalence of the risk factors investigated was higher in males, those aged 41 – 50 and 51 – 60, and healthcare workers in the administrative & support group. The results imply that the prevalence of obesity and hypercholesterolaemia are high among healthcare workers of PKD Segamat. Screening programs, preventative measures and policies must be developed and applied urgently to ensure a healthy workforce within the organization.